The promise of foundational prudence: a response to our critics - Monteiro, Nuno P.; Ruby, Keven G. (International theory, 2009)
Monteiro and Ruby respond to criticisms concerning their international relations (IR) theory and its relationship to the philosophy of science. They believe that a genuine post-foundational IR is possible only once we, as a discipline, recognize the inherent uncertainty of knowledge and the value of multiple approaches in our common endeavor to study international politics. That is the promise of foundational prudence.